A note on computing stokes phase matrices for macroscopically isotropic mirror symmetric scattering medium stokes scattering matrices. (August 2022) - Berk, Alexander
Highlights: Eliminates the need to compute ISM Stokes matrices separately depending on the sign of the scattered minus incident relative azimuth angle. Eliminates the singularity that arises with the traditional formulation for vertical (nadir or zenith) incident or scattered directions. Provides a numerically stable expression for the ISM Stokes matrix elements in the limit as the scattering angle approaches zero. Abstract: Equations used to compute Stokes phase matrices for macroscopically isotropic mirror symmetric scattering medium from Stokes scattering matrices are reformulated to eliminate numerical instability issues and to eliminate the need to treat positive and negative relative azimuth angles as separate cases.